ANALISIS PENGENDALIAN WAKTU DAN BIAYA DENGAN METODE EARNED VALUE MANAGEMENT (EVM) (Studi Kasus: Peningkatan Jalan Patrol – Palintang Kabupaten Bandung) - Ghifari, Rizha Rafli; Sudarsono, Ignatius; Mulyawati, Fauzia (Jurnal Teknik Sipil, 2024)
Project control is a crucial management activity, especially given the complexity of project-related issues. Effective management is needed to ensure that projects, such as the improvement of the Patrol-Palintang road in Bandung Regency, adhere to the planned schedule. The objective of this research is to assess cost and time performance using the Earned Value Management (EVM) method. The data utilized in this study includes the Budget Plan (RAB), S-Curve, Time Schedule, and Weekly Reports. The analysis results from the Earned Value Management method indicate that the time performance is less than one (SPI < 1), with an average SPI value of 0.929. This means that the time performance is poor, indicating delays in project completion relative to the planned schedule. Conversely, the cost performance index is above one, with an average CPI value of 1.0014. This indicates excellent cost performance, as the actual costs incurred are lower than the earned value, demonstrating no wastage of resources.